Struktur, Fungsi, dan Nilai Budaya Legenda Orang Sibunian Gunung Singgalang di Pandai Sikek Tanah Datar - Ayu, Yullya Kartika; Nurizzati, Nurizzati; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was to describe the structure, function, and cultural value of Legend Sibunian Mount Singgalang in Nagari Pandai Sikek Kecamatan X Koto Kabupaten Tanah Datar. This research is a qualitative study using descriptive analysis methods. The data in this study is Legend Sibunian Mount Singgalang. Sources of data in this study is a native who knows exactly about the Legend Sibunian Mount Singgalang in Nagari Pandai Sikek Kecamatan X Koto Kabupaten Tanah Datar. Data was collected techniques using freely refer proficient, proficient techniques, recording techniques, and technical notes. The findings of this study are to description of Legend of the Sibunian Mount Singgalang, structure of Legend Sibunian Mount Singgalang, functions Legend of the Sibunian Mount Singgalang, and cultural value Legend Sibunian Mount Singgalang in Nagari Pandai Sikek Kecamatan X Koto Kabupaten Tanah Datar.